Pengaruh Financial Distress, Pertumbuhan Perusahaan, dan Kualitas Audit Terhadap Opini Audit Going Concern - Ayang Novasya; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study discusses the effect of financial distress, company growth, and audit quality on going concern audit opinion. The population in this study are all manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) in 2015-2019. The number of samples used in this study were 39 companies with purposive sampling technique and the number of observations of research data obtained was 195. The method of data analysis was carried out using logistic regression analysis. The results of the study conclude that financial distress has a negative effect on going-concern audit opinion, company growth has a positive effect on going-concern audit opinion, and audit quality has no effect on going-concern audit opinion.